Respuesta :
Simplifying
13 = 4x + 9
Reorder the terms:
13 = 9 + 4x
Solving
13 = 9 + 4x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-4x' to each side of the equation.
13 + -4x = 9 + 4x + -4x
Combine like terms: 4x + -4x = 0
13 + -4x = 9 + 0
13 + -4x = 9
Add '-13' to each side of the equation.
13 + -13 + -4x = 9 + -13
Combine like terms: 13 + -13 = 0
0 + -4x = 9 + -13
-4x = 9 + -13
Combine like terms: 9 + -13 = -4
-4x = -4
Divide each side by '-4'.
x = 1
Simplifying
x = 1
13 = 4x + 9
Reorder the terms:
13 = 9 + 4x
Solving
13 = 9 + 4x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-4x' to each side of the equation.
13 + -4x = 9 + 4x + -4x
Combine like terms: 4x + -4x = 0
13 + -4x = 9 + 0
13 + -4x = 9
Add '-13' to each side of the equation.
13 + -13 + -4x = 9 + -13
Combine like terms: 13 + -13 = 0
0 + -4x = 9 + -13
-4x = 9 + -13
Combine like terms: 9 + -13 = -4
-4x = -4
Divide each side by '-4'.
x = 1
Simplifying
x = 1